1978
DOI: 10.1172/jci109085
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated resistance to antibiotic synergism in enterococci.

Abstract: A B S T R A C T Mating experiments have shown thathigh-level resistance (minimal inhibitory concentration >2,000 ,uglml) to streptomycin and kanamycin, and resistance to penicillin-streptomycin and penicillinkanamycin synergism are transferable by conjugation from resistant clinical isolates of enterococci to a sensitive recipient strain. Cesium chloride-ethidium bromide ultracentrifugation revealed a satellite (plasmid) band in resistant clinical isolates and the transconjugant strains but not in the sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…Conversely, cells grown in media that permitted less rapid penicillin lysis were less susceptible to spontaneous lysis (Table III). Our studies have demonstrated more rapid and extensive penicillin lysis and killing of S. faecalis than those of most previous investigators (3)(4)(5)(35)(36). We believe that the reasons for these differences include (a) strain variation and (b) differences in the specific testing conditions used.…”
Section: Discussionmentioning
confidence: 48%
“…Conversely, cells grown in media that permitted less rapid penicillin lysis were less susceptible to spontaneous lysis (Table III). Our studies have demonstrated more rapid and extensive penicillin lysis and killing of S. faecalis than those of most previous investigators (3)(4)(5)(35)(36). We believe that the reasons for these differences include (a) strain variation and (b) differences in the specific testing conditions used.…”
Section: Discussionmentioning
confidence: 48%
“…Although ribosomal resistance to streptomycin may account for high-level resistance (MIC, >2,000 pLg/ml) to the drug in a small proportion of clinical isolates (51), in the vast majority of cases highlevel aminoglycoside resistance and subsequent lack of penicillin-aminoglycoside synergism is due to the presence of aminoglycoside-modifying enzymes. Plasmid-mediated enzymes conferring high-level resistance to streptomycin and kanamycin have been recognized for more than a decade (107); by the late 1970s, approximately 50% of enterococcal blood isolates recovered at the Massachusetts General Hospital were highly resistant to streptomycin or kanamycin or both (28) and thus evaded killing by these agents in combination with penicillin.…”
Section: Mechanisms Of Bactericidal Synergismmentioning
confidence: 99%
“…A 45-Mdalton plasmid has been identified in five resistant isolates, which was not present in strains without high-level aminoglycoside resistance; this plasmid was also found in transconjugants of the sensitive recipient strain, after they had acquired high-level aminoglycoside resistance from resistant clinical isolates (8).…”
Section: Introductionmentioning
confidence: 98%
“…Because previous work has demonstrated that highlevel resistance and resistance to synergism were transferable by conjugation into a sensitive recipient strain (8), we have examined a series of Streptococcus fae-calis strains for aminoglycoside-inactivating enzymes: 10 clinical isolates with high-level resistance to streptomycin and kanamycin, a transconjugant strain produced by mating a sensitive recipient with one of the resistant strains, the sensitive recipient, and 5 sensitive clinical isolates were studied. A 45-Mdalton plasmid has been identified in five resistant isolates, which was not present in strains without high-level aminoglycoside resistance; this plasmid was also found in transconjugants of the sensitive recipient strain, after they had acquired high-level aminoglycoside resistance from resistant clinical isolates (8).…”
Section: Introductionmentioning
confidence: 99%